Patients With Very Mild Dementia May Confuse Objective Cognitive Impairments With Subjective Physical Health of Quality of Life: The Tome City Project in Japan - Kasai, Mari; Meguro, Kenichi (Frontiers in Psychology, 2018)
Many elderly people with cognitive dysfunction may observe a decrease in their health levels and quality of life (QOL). The basic concept of QOL consists of several categories including physical functions and mental health. The QOL domain that is most important for elderly people is physical health and, to a lesser extent, psychological health, social relationships, and/ or the environment. Our aim was to explore the relationships between the subjective measure of QOL, an abbreviated version of the World Health Organization Quality of Life (WHOQOL-BREF) scale, and the objective measure of impairment, Clinical Dementia Rating (CDR), among elderly people in a community. Totally, 178 community dwellers aged 75 years and above agreed to participate and completed the WHOQOL-BREF; 66 (32 male, 34 female) scored a CDR of 0 (healthy), 86 (33, 53) scored a CDR of 0.5 (questionable dementia or very mild dementia), and 26 (12, 14) scored a CDR of 1 and above (dementia). According to Pearson’s correlation coefficient analysis (significance level, p<0.05), the physical domain of the WHOQOL-BREF had significant statistical negative correlations with all CDR subscales. The CDR subscale of memory impairment had a significant statistical negative correlation with the WHOQOL-BREF subscales of the physical (r=-0.151, p=0.044) and psychological (r=-0.232, p<0,002) domains. The CDR subscale of home and hobbies impairment had significant statistical negative correlations with all WHOQOL-BREF subscales including the physical (r=-0.226, p=0.002), psychological (r=-0.226, p=0.002), social (r=-0.167, p=0.026), and environmental (r=-0.204, p=0.006) domains. Patients with very mild dementia may confuse cognitive impairment and physical disabilities. In the future, we need to systematically combine memory clinics and all departments related to the elderly for the successful early detection and rehabilitation of, and long-term care for, dementia.